2006
DOI: 10.1080/17402520600877182
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells and Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) is characterized by an immuno-mediated progressive destruction of the pancreatic β cells. Due to the ability of NK cells to kill target cells as well as to interact with antigen-presenting and T cells, it has been suggested that they could be involved in one or multiple steps of the immune-mediated attack that leads to T1D. Abnormalities in the frequency and activity of NK cells have been described both in animal models and patients with T1D. Some of these alterations are linked to its on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…More recently, a larger study confirmed a functional impairment of NK cells in T1D patients, i.e., reduced surface expression of activating receptors and low levels of IFN-and perforin, and suggested that these alterations may be a consequence of T1D, since they are evident exclusively in long-standing disease [359]. It has also been reported that activated NK cells in T1D patients display a reduced expression of NKG2D receptor [357]. It is possible that a downregulation of NKG2D receptor mediates the increased risk for T1D associated with polymorphisms of MHC class I chain-related (MIC) proteins [360] that are NKG2D natural ligands.…”
Section: T Cellsmentioning
confidence: 57%
See 1 more Smart Citation
“…More recently, a larger study confirmed a functional impairment of NK cells in T1D patients, i.e., reduced surface expression of activating receptors and low levels of IFN-and perforin, and suggested that these alterations may be a consequence of T1D, since they are evident exclusively in long-standing disease [359]. It has also been reported that activated NK cells in T1D patients display a reduced expression of NKG2D receptor [357]. It is possible that a downregulation of NKG2D receptor mediates the increased risk for T1D associated with polymorphisms of MHC class I chain-related (MIC) proteins [360] that are NKG2D natural ligands.…”
Section: T Cellsmentioning
confidence: 57%
“…Increased levels of 'Th1 cell'-derived chemokines CCl3, CCl4, and CXCl10 [354,355] and of adhesion molecules ICAM and L-selectin (CD62L) [356] have been found in serum of T1D patients. Several reports have addressed NK population in the peripheral blood of T1D patients [357] and have described a decrease in the peripheral frequency, in most cases temporally related to disease onset [4,281], or a functional deficit [358], but these findings have not been universally replicated [357]. More recently, a larger study confirmed a functional impairment of NK cells in T1D patients, i.e., reduced surface expression of activating receptors and low levels of IFN-and perforin, and suggested that these alterations may be a consequence of T1D, since they are evident exclusively in long-standing disease [359].…”
Section: T Cellsmentioning
confidence: 99%
“…Natural killer cells, a subtype of leukocyte, are known to play an important role in beta-cell destruction and the patho- genesis of diabetes (18). There was a significant increase in natural killer-related genes (KIR2DL4, KLRD1, KLRF1, and NKG7) in response to glucose ingestion, indicating their roles in the pathogenesis of diabetes (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to their role in antimicrobial, antiviral, and antitumor immunity, NK cells have recently also been implicated in inflammatory and autoimmune disorders such as type I diabetes (9,10) and multiple sclerosis (11,12). Genetic variations that influence the proportion of NK cells may also contribute to the clinical outcomes in these diseases.…”
mentioning
confidence: 99%